As demandas judiciais dos trabalhadores santamarienses na busca pela efetividade da CLT entre os anos de 1946 a 1948 - Moraes, Ricardo Aguirre de (2017)
The present paper was developed during the MasterCourse of the Post-Graduate Program in History of the Federal University of Santa Maria, filled in the research line Migratory Flows and Labor. This research aimed to identify and analyze the acting of the worker in the legal environment to validate their rights with the employer through labor lawsuits. Such lawsuits were tried in Santa Maria, during the years 1945, 1946 and 1947, bringing the social counterclaims and struggles used by the workers to guarantee their labor rights during the final period of NewState and the emerging of the re-democratization of the country. The choice of the period analyzed was due to be a period of great changes in the Brazilian political view, focusing on the Constitution of 1946. It was analyzed the way in which the workers of the municipality organized themselves juridically to plead their rights ensured in 1943, during the CLTformalization. This way, the research tried make these individuals express themselves, using as main source of research an important tool to struggle and claim for rights: the labor lawsuits of the Labor Court of Santa Maria.